Modeling and Identification for Pneumatic Control Valves with Stiction. Issue 28 (2015) - Tang, Li; Fang, Lei; Wang, Jiandong; Shang, Qunli
Abstract: Stiction is a common problem in pneumatic control valves. In this work, a new semiphysical model is proposed for sticky pneumatic control valves, based on the basic components of pneumatic control valves, including valve positioner, valve actuator and valve body. The procedure of identifying parameters of the semi-physical model is presented. The semi-physical model contains some major differences with several existing data-driven models in the literature for describing the valve stiction behaviors. Experimental studies are provided to demonstrate the effectiveness of the new semi-physical model and the discrepancies of data-driven models with experimental observations.